2013
DOI: 10.1093/eurheartj/eht270
|View full text |Cite
|
Sign up to set email alerts
|

Sexual counselling for individuals with cardiovascular disease and their partners

Abstract: After a cardiovascular event, patients and their families often cope with numerous changes in their lives, including dealing with consequences of the disease or its treatment on their daily lives and functioning. Coping poorly with both physical and psychological challenges may lead to impaired quality of life. Sexuality is one aspect of quality of life that is important for many patients and partners that may be adversely affected by a cardiac event. The World Health Organization defines sexual health as '… a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(44 citation statements)
references
References 170 publications
3
38
1
2
Order By: Relevance
“…Other studies have reported a decrease in sexual function in women with coronary artery disease 3335 . Older women with heart disease have been reported to engage in sexual activity 36, 37 , and targeted sexual counseling efforts may improve health 38 . Metabolic syndrome in women may be more closely related to coronary artery disease than other cardiovascular outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported a decrease in sexual function in women with coronary artery disease 3335 . Older women with heart disease have been reported to engage in sexual activity 36, 37 , and targeted sexual counseling efforts may improve health 38 . Metabolic syndrome in women may be more closely related to coronary artery disease than other cardiovascular outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Steink and Jaarsma (2015) pointed out that giving advice to the patients with MI and their spouses could be effective in relieving their anxiety and fear of sexual activity (26). Steinke et al (2013) conducted a study including a social-cognitive intervention. The intervention consisted of watching a video at home about resuming sexual activity by patients and their spouses, telephone counseling within four to six weeks after MI, and sending some emails within four to six weeks after MI.…”
Section: Discussionmentioning
confidence: 99%
“…Sex education can be effective for reducing the anxiety of patients (20). During rehabilitation, sexual concerns are one of the most common stressors among spouses of patients (21), thus it is important to include patients and their spouses in sex education programs (22). However, for various reasons, such as culture and modesty, sex education and its importance is neglected by health teams (19); the majority of researches show that patients and their families regretted that the treatment team members had not discussed sexual function with them after an MI.…”
Section: Introductionmentioning
confidence: 99%
“…Some patients with HF might need specific information about activities they can undertake, as well as clear information and treatment to help cope with sexual problems 30. Because sexual problems might occur during the disease trajectory, sexual concerns need to be discussed more than once during treatment and should become an integral part of HF management and patient education.…”
Section: Counselling and Treatment For Sexual Problems In Heart Failumentioning
confidence: 99%
“…This information needs to be adapted to the personal situation of patients, sexual preferences, and culture 30, 31. One of the approaches that can be used to guide health professionals in determining needs of patients and in providing information related to sexuality is the so‐called PLISSIT model32 ( Figure  2).…”
Section: Counselling and Treatment For Sexual Problems In Heart Failumentioning
confidence: 99%